1998
DOI: 10.1074/jbc.273.50.33354
|View full text |Cite
|
Sign up to set email alerts
|

Cis-activation of L1-mediated Ankyrin Recruitment by TAG-1 Homophilic Cell Adhesion

Abstract: Neural cell adhesion molecules (CAMs) of the immunoglobulin (Ig) superfamily mediate not only cell aggregation but also growth cone guidance and neurite outgrowth. In this study we demonstrate that two neural CAMs, L1-CAM and TAG-1, induce the homophilic aggregation of Drosophila

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0
5

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 35 publications
2
54
0
5
Order By: Relevance
“…Following homophilic binding, CAMs of the L1 family transduce signals resulting in the recruitment of ankyrin and spectrin to points of cell-cell contact (13)(14)(15)(16)(17). Drosophila S2 cells are a classic model system in which potential CAMs have been tested for these properties (14,27).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Following homophilic binding, CAMs of the L1 family transduce signals resulting in the recruitment of ankyrin and spectrin to points of cell-cell contact (13)(14)(15)(16)(17). Drosophila S2 cells are a classic model system in which potential CAMs have been tested for these properties (14,27).…”
Section: Resultsmentioning
confidence: 99%
“…These antibodies were described in a previous publication (11). Mouse anti-Drosophila ankyrin antibodies were generated as described previously (17). ␣-Amanitin was obtained from Sigma.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, it has been shown that ankyrinB binding promotes neuritogenesis by coupling L1CAM to the actin cytoskeleton (Nishimura et al, 2003). Binding L1CAM to ankyrinG, conversely, is thought to recruit L1CAM to the AIS, a highly specialized compartment in the proximal axon where APs are generated (Malhotra et al, 1998;Yoshimura and Rasband, 2014). Both ankyrins are thought to recruit and compartmentalize L1CAM and other L1CAM family members, such as neurofascin Boiko et al, 2007).…”
Section: Discussionmentioning
confidence: 99%